On the search for the chiral anomaly in Weyl semimetals: the negative longitudinal magnetoresistance - R D dos Reis; M O Ajeesh; N Kumar; F Arnold; C Shekhar; M Naumann; M Schmidt; M Nicklas; E Hassinger (New Journal of Physics, 2016)
Recently, the existence of massless chiral (Weyl) fermions has been postulated in a class of semi-metals with a non-trivial energy dispersion. These materials are now commonly dubbed Weyl semi-metals (WSM). One predicted property of Weyl fermions is the chiral or Adler–Bell–Jackiw anomaly, a chirality imbalance in the presence of parallel magnetic and electric fields. In WSM, it is expected to induce a negative longitudinal magnetoresistance (MR). Here, we present experimental evidence that the observation of the chiral anomaly can be hindered by an effect called ‘current jetting’. This effect also leads to a strong apparent negative longitudinal MR, but it is characterized by a highly non-uniform current distribution inside the sample. It appears in materials possessing a large field-induced anisotropy of the resistivity tensor, such as almost compensated high-mobility semimetals due to the orbital effect. In case of a non-homogeneous current injection, the potential distribution is strongly distorted in the sample. As a consequence, an experimentally measured potential difference is not proportional to the intrinsic resistance. Our results on the MR of the Weyl semimetal candidate materials NbP, NbAs, TaAs, and TaP exhibit distinct signatures of an inhomogeneous current distribution, such as a field-induced ‘zero resistance’ and a strong dependence of the ‘measured resistance’ on the position, shape, and type of the voltage and current contacts on the sample. A misalignment between the current and the magnetic-field directions can even induce a ‘negative resistance’. Finite-element simulations of the potential distribution inside the sample, using typical resistance anisotropies, are in good agreement with the experimental findings. Our study demonstrates that great care must be taken before interpreting measurements of a negative longitudinal MR as evidence for the chiral anomaly in putative Weyl semimetals.